PENGEMBANGAN MEDIA PEMBELAJARAN ARTS BERBASIS ANDROID PADA MATERI TATA SURYA UNTUK SMP - Pratama, Yoga; Akhlis, Isa; Linuwih, Suharto (UPEJ Unnes Physics Education Journal, 2020)
The solar system is one of the physics subject matter that seems abstract because it deals with celestial objects that cannot be presented in class. This research develops learning media with Android-based augmented reality technology. The purpose of this research is to develop an Android-based arts learning media on solar system subject matter for junior high school and find out the feasibility of the learning media. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of this research are learning media products for Android-based which have been tested on 5 groups of respondents using the questionnaire method. From the results of the feasibility test obtained a percentage of 84,71%. Based on the results obtained, the ARTS learning media was declared suitable for use.